LITERASI KEUANGAN DAN PERBANKAN DIGITAL UNTUK MENJADIKAN ANGGOTA UMKM BANKABLE DI CINERE, JAWA BARAT - Siti Hidayati; Marlina Marlina; Dewi Cahyani Pangestuti (Jurnal Abdimas Bina Bangsa, 2023)
The Community Engagement Program aims to provide financial literacy and assistance in business transaction record-keeping to members of Small and Medium Enterprises (SMEs) in Cinere Subdistrict. A participatory approach is employed to encourage participants' engagement in understanding digital financial services and banking, as well as effectively managing business transactions. The activities involve 27 SME members, the outreach team, and Bank Syariah Indonesia Branch of Fatmawati. Financial literacy is conducted through pre-test and post-test assessments to measure knowledge enhancement. From the pre-test, some participants already have bank accounts and e-wallets, although comprehension of digital services still varies. Post-test results indicate a significant improvement, reaching 100% understanding of digital services and the importance of safeguarding personal data. Business transaction record-keeping assistance is conducted using Excel format and a manual approach, aiding participants in better managing their businesses. Results demonstrate enhanced administrative skills and transaction management. Additionally, the socialization of KUR (Kredit Usaha Rakyat) provides a safer funding option for SMEs. Recommendations for the future encompass strengthened collaboration with financial institutions, continuous mentoring, more in-depth impact assessment, and group learning. This program has the potential to fortify the SME sector, enhance financial literacy, and support community economic growth in the dynamic era of technology and economics. By actively involving SME members and providing sustained mentoring, the program yields tangible benefits for the development of small and medium enterprises, enhancing their competitiveness in an increasingly competitive market